Smart PDP: processo de desenvolvimento de produtos da indústria de autopeças no contexto da indústria 4.0 - Benetti, Vanderlei Giovani (Universidade do Vale do Rio dos Sinos, 2021)
The automotive industry is one of the most important worldwide drivers of growth, employment, and innovation. The intense globalization and the growth of individualization, digitization and greater competition in the sector put pressure on the participants in this chain. At the same time, Industry 4.0 emerges as a new paradigm for the industry. The concepts of the Fourth Industrial Revolution involve the integration of physical and digital technologies at all stages of the product lifecycle. The integration between these factors provides more customization to the production and to the product, reducing product development time and the time needed to start selling. In this scenario, changes related to the product, market, business processes and technologies characterize the challenging context presented by Industry 4.0 to the auto parts industry today. Therefore, the objective of this research is to adapt the PDP - Product Development Process for the auto parts industry to the current context of Industry 4.0. To achieve this goal, the research methodology chosen was DSR -Design Science Research. Seeking to develop a satisfactory solution to the research problem, the strategy adopted was to use the APQP (Advanced Product Quality Planning) as a basis for building an artifact, and to explore process elements (structure, stages, interactions, management) and technology (tools, techniques and technologies) to be incorporated into the proposed PDP. The artifact’s development had suggestions identified in the literature, and also in the data collection stages with professionals and experts with experience in the PDP of the automotive chain. At the end, the artifact was submitted to a Focus Group, which was the technique chosen for the qualitative assessment of the artifact. The proposed artifact, called Smart PDP, stands out with the following characteristics and contributions to the auto parts industry: I) integration of technologies and elements from Industry 4.0, using the Digital Twin approach to support the definition, development and validation of the virtual design of the product and manufacturing processes; II) adoption Project Gates at 4 critical moments to achieve the project objectives; III) use of the Kanban methodology for project management; IV) organization the manufacturing process implementation activities with Try-Out Sprints and V) integration a management flow of Lessons Learned and Improvement Opportunities identified during the projects.
Keywords: Processo de desenvolvimento de produtos; Indústria 4.0; Indústria de autopeças; Smart PDP; Product development process; Industry 4.0; Auto parts industry; ACCNPQ::Engenharias::Engenharia de Produção